RASA1 Mutations and Associated Phenotypes in 68 Families with Capillary Malformation–Arteriovenous Malformation. Issue 12 (10th October 2013) - Revencu, Nicole; Boon, Laurence M.; Mendola, Antonella; Cordisco, Maria Rosa; Dubois, Josée; Clapuyt, Philippe; Hammer, Frank; Amor, David J.; Irvine, Alan D.; Baselga, Eulalia; Dompmartin, Anne; Syed, Samira; et al.
<x xml:space="preserve">Abstract</x> Capillary malformation‐arteriovenous malformation (CM‐AVM) is an autosomal‐dominant disorder, caused by heterozygous RASA1 mutations, and manifesting multifocal CMs and high risk for fast‐flow lesions. In this study we showed that RASA1 mutations are specifically identified in patients with CM‐AVM, in about 2/3 of them. The phenotypes and genotypes of 68 novel families are reported. This study expands the phenotypic spectrum to include zones of numerous small pale halos with central punctate red spots in the extremities. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>